2007
DOI: 10.1161/strokeaha.107.183689
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Management of Spontaneous Intracerebral Hemorrhage in Adults

Abstract: Purpose-The aim of this statement is to present current and comprehensive recommendations for the diagnosis and treatment of acute spontaneous intracerebral hemorrhage. Methods-A formal literature search of Medline was performed through the end date of August 2006. The results of this search were complemented by additional articles on related issues known to the writing committee. Data were synthesized with the use of evidence tables. The American Heart Association Stroke Council's Levels of Evidence grading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
385
1
44

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(432 citation statements)
references
References 202 publications
2
385
1
44
Order By: Relevance
“…This is an important question clinically, as the presence of perihematomal ischemia would favor a role for surgery and argue against blood pressure lowering to prevent hematoma expansion on the grounds that this may exacerbate perihematomal hypoperfusion (Broderick et al, 2007). Animal studies initially suggested the existence of an ischemic penumbra evidenced by decreased perihematomal blood flow (Bullock et al, 1988;Mendelow et al, 1984).…”
Section: A Perihematomal Penumbramentioning
confidence: 99%
“…This is an important question clinically, as the presence of perihematomal ischemia would favor a role for surgery and argue against blood pressure lowering to prevent hematoma expansion on the grounds that this may exacerbate perihematomal hypoperfusion (Broderick et al, 2007). Animal studies initially suggested the existence of an ischemic penumbra evidenced by decreased perihematomal blood flow (Bullock et al, 1988;Mendelow et al, 1984).…”
Section: A Perihematomal Penumbramentioning
confidence: 99%
“…American Heart Association/American Stroke Association (AHA/ASA) guidelines 17 and the Japanese Guidelines for the Management of Stroke 2004 18 both recommend lowering of BP for ICH patients with systolic blood pressure (SBP) of 4180 mm Hg or mean arterial pressure of 4130 mm Hg. The target BP level has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the data available from well designed studies, especially from the Surgical Trial in Intracerebral Haemorrhage (STICH), there is incertitude about which is the proper treatment in a particular patient with spontaneous supratentorial intracerebral haemorrhage 3,6,8,15,16,17,18,19,21,22 . The variability among patients, as well as the great number of factors that influence their outcome, are important issues to take into account.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that this condition affects 10-20 in 100 000 people every year with a mortality between 23-58% 1,13,20,21 . Additionally, only one of five of the survivors regain functional independence at 6 months after ictus 3,13,14,15,20 . There is no definitive evidence to guide treatment but recommendations 15,16,20 .…”
Section: Introductionmentioning
confidence: 95%